Carbon sequestration potential of biochar for sustainable agriculture - Yoganivashini, R; Baskar, K; Jothimani, S; Jeberlin, P B; Manikandan, K; Arumugam, P M; Aakash, R (Plant Science Today, 2025)
Biochar, a carbon-rich product from biomass pyrolysis, presents a promising solution for sustainable agriculture, particularly in long-term carbon sequestration and soil enhancement. Its durability enables it to persist in soils for extended periods, functioning as a permanent carbon sink and helping to reduce atmospheric CO2 levels. The stability and carbon sequestration potential of biochar is influenced by factors such as the type of feedstock used, pyrolysis conditions, soil characteristics and environmental factors. Incorporating biochar into sustainable agricultural practices, such as conservation tillage, cover cropping and agroforestry, can significantly improve soil health and carbon storage. Additionally, biochar contributes to soil quality by minimizing nutrient leaching and runoff, controlling erosion and aiding in soil restoration efforts. While biochar provides a range of environmental and agricultural benefits, further research is necessary to optimize its production, application, integration and stability across diverse landscape conditions.